PERANCANGAN PROMOSI OBJEK WISATA NAGARI SULIK AIA KABUPATEN SOLOK MELALUI MEDIA WEBSITE - YULIA PUTRI MAYASARI, Dr. Budiwiran, M.Pd., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this design are to inform and promote tourist attraction of Sulik Aia in Solok District to the tourists through website media, thus tourists can get to know and visit those tourist attractions. Website is one of the effective media for doing promotion and socialization. Website can accommodate a lot of information in a coherent and structured manner.Method that used in this design was the Glass Box method. The design process began by collecting data through observation, interviews and documentation. This design used SWOT data analysis method to analyze the strengths, weaknesses, opportunities, and threats.Based on the results of the tourist attraction promotion design in Sulik Aia Nagari through the website media, it can be concluded that in the making of a design, there are some fundamental and substansial things needed as a guide in conducting online promotions. Design of promotions through this website has consider the shape, size, colors, and typography in order to achieve the intended purpose in a promotion. Website is one of the effective media in conducting promotions. The supporting media used in this design consisted of x-banners, posters, T-shirts, stickers, mugs, bags and tickets.Keywords: planning, promotion, tourism, website